The monastic order in Yorkshire, 1069-1215 - Burton, Janet (Cambridge studies in medieval life and thought, 1999)
This 1999 book explores the dramatic growth of the monastic order in Yorkshire from the foundation of the first post-Conquest abbey at Selby in 1069 to 1215. The first half examines the dynamics of monastic expansion, discussing the influences on both its chronological development and its geographical pattern. It demonstrates that the monastic expansion owed much to the particular political and tenurial conditions which existed in the century after 1069: the establishment of Norman political ascendancy, the extension of central government under Henry I, and the civil war of the reign of King Stephen. The second part of the book explores recruitment, patronage, economy and cultural life. Particular attention is paid to the role of women in the religious life. Nunneries, so often regarded as second-class or failed monasteries, are here shown to have had a distinctive function in society, in terms both of recruitment and of interaction with the local community.